Nanoplasmonic ruler for measuring separation distance between supported lipid bilayers and oxide surfaces - Abdul Rahim Ferhan (2020)
Unraveling the details of how supported lipid bilayers (SLBs) are coupled to oxide surfaces is experimentally challenging, and there is an outstanding need to develop highly surface-sensitive measurement strategies to determine SLB separation distances. Indeed, subtle variations in separation distance can be associated with significant differences in bilayer–substrate interaction energy. Herein, we report a nanoplasmonic ruler strategy to measure the absolute separation distance between SLBs and oxide surfaces. A localized surface plasmon resonance (LSPR) sensor was employed to track SLB formation onto titania- and silica-coated gold nanodisk arrays. To interpret measurement data, an analytical model relating the LSPR measurement response to bilayer–substrate separation distance was developed based on finite-difference time-domain (FDTD) simulations and theoretical calculations. The results indicate that there is a larger separation distance between SLBs and titania surfaces than silica surfaces, and the trend was consistent across three tested lipid compositions. We discuss these findings within the context of the interfacial forces underpinning bilayer–substrate interactions, and the nanoplasmonic ruler strategy provides the first direct experimental evidence comparing SLB separation distances on titania and silica surfaces.